Faith in Contention: Explaining the Salience of Religion in Ethnic Conflict. (February 2017) - Isaacs, Matthew
What explains variation in the role of religion in ethnic conflict? Although conflict involving religion is often more violent and longer lasting than other forms of conflict, to date little research has examined the factors explaining the relevance of religion to conflict mobilization. Adopting a rational choice approach, I argue that religion is more likely to be a salient component of conflict when an ethnic group's religious leaders face local incentives to compete over adherents. I test this approach using a multi-method research design that combines statistical analysis of original time-series data on the salience of religion in conflict with qualitative evidence drawn from the Troubles in Northern Ireland. Both types of analyses support the notion that competition among religious leaders can serve as a precursor to the mobilization of religious sentiment in conflict, which in turn exerts a tremendous influence on the intensity and duration of conflict.